Thermal Aeroelastic Tailoring for Laminated Panel with Lamination Parameters and JAYA Algorithm - Peng Jin; Qihao Zheng; Wei Wei (International Journal of Aerospace Engineering)
This work investigates thermal aeroelastic tailoring of a laminated composite panel with a lamination parameter-based method. Equivalent membrane and bending coefficients of thermal expansions for symmetric laminated panel are derived and represented with lamination parameters using Classical Laminated Plate Theory. The relationship between thermal flutter behavior and lamination parameters is examined. The optimization process is split into two stages. In the first stage, lamination parameters and laminate thicknesses are as design variables to minimize the structure mass, subject to thermal flutter behavior and feasible region constraints of lamination parameters. In the second-stage, instead of using conventional genetic algorithm, the enhanced JAYA method is extended to search the laminate configuration to target the optimal lamination parameters. The effectiveness of the presented method is demonstrated through a thermal aeroelastic tailoring problem.